Breast conservation in ductal carcinoma in situ (DCIS): what defines optimal margins?. Issue 5 (20th December 2016) - Toss, Michael S; Pinder, Sarah E; Green, Andrew R; Thomas, Jeremy; Morgan, David A L; Robertson, John F R; Ellis, Ian O; Rakha, Emad A
Abstract : The introduction of mammographic screening has resulted in a rise in the detection rate of ductal carcinoma in situ (DCIS), currently accounting for one‐fifth of screen‐detected breast cancers. Although 60–70% of DCIS are treated with breast‐conserving surgery (BCS) with or without radiotherapy, the frequency of subsequent surgery to re‐excise positive margins in order to reduce the probability of recurrences remains high. DCIS recurrence is associated not only with financial, health and psychological implications; approximately half these recurrences are invasive disease. An appropriate margin width for patients undergoing BCS for invasive breast cancer has been largely agreed. Although there is a perception that such recommendations may be applicable to DCIS, major differences exist which may affect this application. Importantly, DCIS patients often do not receive systemic adjuvant (endocrine) therapy and not all receive radiotherapy in routine practice. There is evidence that wide margins (i.e. >10 mm) confer better protection against recurrence than positive (i.e. 0 mm) margins; however, there remains a debate concerning the optimum margin width between 0 and 10 mm. Previous studies have demonstrated that radiation therapy may not compensate for lack of re‐excision in those patients with positive or close margins, while wide margins will inevitably compromise cosmesis and patients' body image perception. This review aims to address the clinical question of the minimal margin width in DCIS treated with BCS that is associated with the lowest recurrence rate and when, therefore, further surgical intervention for re‐excision can be safely avoided. A range of clinical circumstances that might affect this are considered.